STRATEGIES TO ENHANCE (FINANCIAL MANAGEMENT) EFFICIENCY IN THE PUBLIC SECTOR IN IRAQ: LESSONS FROM BEST INTERNATIONAL PRACTICES - Russul Esam Nori (Scholars Digest Publishing, 2024)
This research paper examines the implementation and outcomes of adopting international best practices in financial management in the Iraqi Ministry of Health. The practical application focused on three key strategies: accrual accounting, integrated financial management information systems (IFMIS) and participatory budgeting. The aim of the study was to improve the accuracy of financial reporting, improve transparency and increase stakeholder satisfaction. The hands-on experiment demonstrated significant improvements, including an increase in budget adherence from 65% to 85%, a reduction in financial reporting errors from 15% to 5%, and an increase in stakeholder satisfaction from 40% to 70%. These results suggest that with the right adjustments, these global strategies can be successfully applied to improve public finance management in Iraq, contributing to greater economic stability and public confidence.
Keywords: Accrual accounting, IFMIS, participatory budgeting, financial management, public sector, Iraq, budget adherence, transparency, stakeholder satisfaction, international best practices.